UMPSA equipped with state-of-the-art facilities will produce successful engineers - Hafizatulazlin, Abdul Aziz (UMPSA, 2023)
GAMBANG, 21 October 2023 - A graduand of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Pagie Lau Ting Ying from Miri, Sarawak received the Presidential Academic Excellence Prize from the Board of Engineers Malaysia (BEM) at the UMPSA 18th Convocation Ceremony held at the UMPSA Sports Complex Hall, Gambang Campus.